Pemanfaatan Bahan Bekas sebagai Alat Peraga IPA Ramah Lingkungan - Silviana, Fitria; Prayogi, Soni (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2023)
Effective learning can be achieved by utilizing practical teaching aids that can challenge students to understand the material. This needs to be done to increase students' lack of learning motivation, as it will hurt learning achievement. Each student has a variety of learning styles, such as visual, audio, and kinesthetic. Therefore, teachers should try to create innovation by developing teaching aids in the form of a Pascal pressure model that can be implemented in learning experiments. The purpose of making this demonstration equipment is so students can understand the concept of Pascal pressure more concretely and in-depth, compared to relying on pictures as a visual tool. Apart from that, this innovation can also increase student motivation so that learning becomes more real and not just imagination and so that student learning outcomes can increase. The research method involves identifying old materials that can be used, designing creative and educational teaching aids, as well as testing the effectiveness of teaching aids in supporting science learning. The research results show that using used materials in natural science teaching aids can reduce negative environmental impacts by reducing waste and consuming new resources. The teaching aids developed can also facilitate understanding of science concepts visually and interactively. The trial of this teaching aid showed a positive response from students toward a more interesting and sustainable learning method.